Four new records for the Honduran flora and a preliminary checklist of pteridophytes and lycophytes for the Río Plátano Man and Biosphere Reserve, Honduras - Reyes-Chávez, Johan David; Rojas-Alvarado, Alexander; Reyes-Calderon, Onán (Instituto de Ecología, A.C., 2019)
Background and Aims: The group of pteridophytes and lycophytes has been understudied in Honduras, which can be observed in the Río Plátano Man and Biosphere Reserve (RPHBR) that only has 44 species reported. The objective of this study is to present a preliminary list of these groups, counting the species found in archaeological sites within the department of Gracias a Dios and presenting four new records for the flora of Honduras.Methods: As part of floristic inventories realized between August 2016 and September 2017, a total of 58 species of pteridophytes and lycophytes not previously reported for the RPHBR were collected and identified in the municipality of Brus Laguna, the species names were updated, and the species present in the protected area were cataloged.Key results: The ferns reported for the RPHBR increased to 103 species, which represents an increase of 131% and three new records of the genus Tectaria and one of Adiantum are added for Honduras.Conclusions: The diversity of these groups stands out in little altered areas within the RPHBR, especially along the rivers. However, there is also a lack of information in the areas close to the towns, that are currently altered and need protection and research.